KENDALA PEMERINTAH KOTA PADANG DALAM MENANGGULANGI BENCANA ABRASI SEPANJANG KAWASAN PANTAI PURUS DI KOTA PADANG - Desi Marlina; Zikri Alhadi (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2020)
Indonesian is a country that has very many islands and has the longest coastline after Canada. Of the many islands located in the territory of Indonesia, not all of the beaches are well preserved, even many of the beaches have suffered damage caused by coastal abrasion, one of which is the purus beach in the city of Padang. Abrasion is an erosion that often occurs in coastal areas caused by ocean waves over a long period of time and can also be caused by human activity itself. The purpose of this research is to determine the obstacles faced by the Padang city government in overcoming abrasion disasters along the purus beach area in the city of Padang. The results show that there are several obstacles that are being faced by the Padang city government in overcoming the abrasion disaster, namely the funds owned by the Padang city government are insufficient in carrying out abrasion disasters and the equipment used is also very limited so that the Padang city government in dealing with abrasion disasters on the coast purus according to the existing equipment.